Multilayer carbon nanotube assembly, multilayer carbon nanotube dispersion, conductive material, electrode, secondary battery, planar assembly, filter, electromagnetic wave-shielding and pellicle for extreme-ultraviolet light

A multi-walled carbon nanotube aggregate with controlled length and Fe content addresses the issues of conductivity and dispersibility, enabling effective integration into conductive materials and various applications.

JP2025010480APending Publication Date: 2025-01-21SUMITOMO CHEM CO LTD

Patent Information

Application Number
JP2024058118
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-07
Filing Date
2024-03-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing carbon nanotube aggregates face challenges with high conductivity and poor dispersibility in dispersion media, making them difficult to handle and integrate into applications effectively.

Method used

A multi-walled carbon nanotube aggregate with a maximum length of 1000 μm to 30000 μm and a controlled Fe atom content of 0.5% to 10% by mass, which enhances both conductivity and dispersibility, allowing for stable entanglement and improved interaction with dispersion media.

Benefits of technology

The solution provides a carbon nanotube aggregate with high conductivity and good dispersibility, facilitating its use in conductive materials, electrodes, secondary batteries, filters, electromagnetic shields, and extreme ultraviolet ray pellicles by ensuring effective integration and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010480000002
    Figure 2025010480000002
  • Figure 2025010480000001
    Figure 2025010480000001
Patent Text Reader

Abstract

To provide a multilayer carbon nanotube assembly having high conductivity and excellent dispersibility to a dispersant, a multilayer carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SOLUTION: A multilayer carbon nanotube assembly includes a multilayer carbon nanotube with a maximum length of 1000 to 30000 μm and an Fe atom, in which a content ratio of the Fe atom to a total mass of the assembly is 0.5 mass% or more and less than 10 mass%. There are also provided a multilayer carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a multi-walled carbon nanotube aggregate, a multi-walled carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar aggregate, a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet rays. [Background technology]

[0002] Carbon nanotubes have good mechanical and electronic properties and are expected to be used in a variety of applications. Known carbon nanotubes (hereinafter sometimes referred to as "CNT") include single-walled carbon nanotubes (hereinafter sometimes referred to as "SWCNT") and multi-walled carbon nanotubes (hereinafter sometimes referred to as "MWCNT"), which are several μm to several tens of μm in length. SWCNTs are seamless cylindrical tubes formed from a single layer of graphene and have a high specific surface area, which makes them promising for high electrical conductivity, and they are therefore attracting attention as a conductive additive. On the other hand, MWCNTs are made up of multiple layers of concentric cylindrical tubes stacked together, with some MWCNTs consisting of dozens of layers. MWCNTs have a larger cylindrical tube diameter and a smaller specific surface area than SWCNTs, making them slightly easier to handle than SWCNTs. However, it is difficult to achieve electrical conductivity as high as that of SWCNTs. Furthermore, CNTs having a length of several μm to several tens of μm are in powder form and are mainly composed of carbonaceous matter, so that they are basically difficult to handle, and the dispersibility of CNTs in a dispersion medium is an issue.

[0003] In recent years, longer CNTs, specifically long fiber MWCNTs with lengths of several mm, have been attracting attention. Although long fiber MWCNTs have a low specific surface area, they are expected to have higher electrical conductivity than short MWCNTs due to their long length. In addition, they are easier to handle than powdered CNTs. Long fiber MWCNT has traditionally been difficult to manufacture, but in recent years, production technologies have been developed and it is expected that they will become easier to obtain.

[0004] For example, a method has been proposed in which a plurality of CNTs are aligned in the longitudinal direction and collected to obtain a long CNT assembled wire or a CNT assembled wire bundle (see, for example, Patent Document 1). According to the technology described in Patent Document 1, it is stated that the length of the CNT assembled wire can be made 10 cm or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2020 / 138379 Summary of the Invention [Problem to be solved by the invention]

[0006] The CNT aggregate obtained by the technique described in Patent Document 1 includes an aggregate of long fibers formed by oriented CNT fibers. Patent Document 1 does not focus on dispersibility in a dispersion medium, which is important for the application of CNTs.

[0007] An object of the present disclosure is to provide a multi-walled carbon nanotube aggregate having high electrical conductivity and good dispersibility in a dispersion medium, and a conductive material, an electrode, a secondary battery, and a planar aggregate each including the multi-walled carbon nanotube aggregate. A problem to be solved by another embodiment of the present disclosure is to provide a multi-walled carbon nanotube dispersion containing an aggregate of multi-walled carbon nanotubes having high electrical conductivity. The problem to be solved by yet another embodiment of the present disclosure is to provide a planar aggregate containing multi-walled carbon nanotube powder, a filter, an electromagnetic wave shield, and an extreme ultraviolet pellicle using the planar aggregate. [Means for solving the problem]

[0008] <1> A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm and Fe atoms, the content of the Fe atoms being 0.5 mass % or more and less than 10 mass % with respect to the total mass of the aggregate. <2> Conductive additive <1> The multi-walled carbon nanotube aggregate according to claim 1. <3> <1> or <2> 2. A multi-walled carbon nanotube dispersion comprising the multi-walled carbon nanotube aggregate according to claim 1 and a dispersion medium. <4> <1> or <2> A conductive material comprising the multi-walled carbon nanotube aggregate according to claim 1. <5> An ink composition for forming a negative electrode of a lithium battery <3> The multi-walled carbon nanotube dispersion liquid according to claim 1. <6> An electrode active material; <4> and an electrode comprising the conductive material according to claim 1. <7> <6> A secondary battery comprising the electrode according to claim 1. <8> A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and Fe atoms, the content ratio of the Fe atoms being 0.5 mass % or more and less than 10 mass % with respect to the total mass of the aggregate. <9> <1> , <2> or <8> A planar aggregate comprising the multi-walled carbon nanotube aggregate according to claim 1. <10> <9> A filter using the planar assembly described in . <11> <9> Electromagnetic wave shielding using the planar assembly described in 1. <12> <9> A pellicle for extreme ultraviolet light using the planar assembly described in claim 1. Effect of the Invention

[0009] According to an embodiment of the present disclosure, it is possible to provide a multi-walled carbon nanotube aggregate having high electrical conductivity and good dispersibility in a dispersion medium, a conductive material, an electrode, a secondary battery, and a planar aggregate each including the multi-walled carbon nanotube aggregate. According to another embodiment of the present disclosure, a multi-walled carbon nanotube dispersion including an aggregate of multi-walled carbon nanotubes having high electrical conductivity can be provided. According to yet another embodiment of the present disclosure, it is possible to provide a planar aggregate containing multi-walled carbon nanotube powder, a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet radiation using the planar aggregate. [Brief description of the drawings]

[0010] [Figure 1] 1 is a scanning electron microscope photograph showing one embodiment of a multi-walled carbon nanotube aggregate according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0012] <Multi-walled carbon nanotube aggregate: First embodiment> The multi-walled carbon nanotube aggregate of the present disclosure includes multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm and Fe atoms, and the content ratio of Fe atoms to the total mass of the aggregate is 0.5 mass % or more and less than 10 mass %. The multi-walled carbon nanotube aggregate of the present disclosure may be in the form of a sheet, fiber, or the like. can. Here, the sheet-like aggregate means that the aggregate of multi-walled carbon nanotubes has a sheet-like form. The fibrous aggregate means that the multi-walled carbon nanotubes have a thread form. The fibrous aggregate may contain the multi-walled carbon nanotubes in a monofilament (single fiber) state or in a multifilament state, that is, in a thread state in which a plurality of multi-walled carbon nanotube fibers are twisted together.

[0013] [Multi-walled carbon nanotubes] The aggregate of multi-walled carbon nanotubes of the present disclosure (hereinafter, may be simply referred to as "aggregate of the present disclosure") includes multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm. Hereinafter, "multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm" may be abbreviated as "ULMWCNT". ULMWCNT has a maximum length of 1000 μm to 30000 μm, which is longer than the general-purpose MWCNT and can take the form of fibers. Here, the term "fiber" is used generally to refer to a structure in which one dimension is greater than the other two. The fibers may be thread-like fibers with a circular cross section, ribbon-like fibers with a rectangular cross section, hollow, or have other shapes. From the viewpoint of increasing the electrical conductivity of the aggregate of the present disclosure, the cross section of the ULMWCNT is preferably circular and is preferably hollow.

[0014] By taking on a fibrous shape, ULMWCNTs have the property of easily entangling with one another. The aggregate of the present disclosure includes at least one ULMWCNT, and from the viewpoint that the MWCNTs are easily entangled with one another to form a more stable aggregate, it is preferable that the aggregate is an aggregate including a plurality of ULMWCNTs. Hereinafter, an aggregate including ULMWCNTs may be abbreviated as "ULMWCNT aggregate." The aggregates of the present disclosure may be aggregates of intertwined three-dimensional structures. Fig. 1 is a scanning electron microscope (SEM) photograph showing one embodiment of the aggregate of the present disclosure. The SEM photograph shown in Fig. 1 shows that a plurality of fibrous ULMWCNTs are entangled to form a sheet-like aggregate. In this manner, the entangled state of the ULMWCNTs in the aggregate of the present disclosure can be confirmed by SEM observation.

[0015] The length of ULMWCNTs can be measured by focusing on one ULMWCNT and observing multiple SEM images with adjacent viewing angles. Here, length refers to the length of the ULMWCNT in the longitudinal direction, and the maximum value of the measured length is taken as the "maximum length." As described above, when a single ULMWCNT with a maximum length in the range of 1000 μm to 30000 μm is observed within the viewing angle of the SEM photograph, it can be confirmed that the observed aggregate is the aggregate of the present disclosure.

[0016] As described above, it is preferable that a plurality of ULMWCNTs having a maximum measured length in the range of 1000 μm to 30000 μm are present within the viewing angle of the SEM photograph. Using the above method, focusing on 100 MWCNTs included in the viewing angle of the SEM photograph, the maximum length of each is measured, and from the viewpoint of further improving the stability of the aggregate due to the entanglement of ULMWCNTs, it is preferable that 10% or more of the observed MWCNTs have a maximum length in the range of 1000 μm to 30,000 μm, calculated as the number, of which 20% or more is more preferable, 30% or more is even more preferable, and 50% or more is particularly preferable.

[0017] The diameter of ULMWCNT is measured by observing SEM or transmission electron microscope (TEM) images. Here, the diameter refers to the length in the direction perpendicular to the longitudinal direction of the ULMWCNT, and the diameter is measured at 10 different points on one ULMWCNT, and the average value is taken as the diameter of that ULMWCNT.

[0018] The length of the ULMWCNTs contained in the aggregate of the present disclosure is in the range of 1000 μm to 30000 μm, preferably in the range of 1050 μm to 25000 μm, more preferably in the range of 1100 μm to 20000 μm, even more preferably in the range of 1200 μm to 18000 μm, and particularly preferably in the range of 1300 μm to 15000 μm. The diameter of the ULMWCNTs contained in the aggregate of the present disclosure is preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, even more preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0019] The length / diameter ratio of the ULMWCNT, so-called aspect ratio, is preferably 1,000 or more, more preferably 3,000 or more, further preferably 5,000 or more, and particularly preferably 10,000 or more. The aspect ratio can be calculated from the ratio of the maximum length to the diameter of one ULMWCNT. From the viewpoint of measurement accuracy, it is preferable to use the average value of the measurements of 20 or more ULMWCNTs.

[0020] From the viewpoint of dispersibility, the specific gravity of the ULMWCNT aggregate is preferably in the range of 1.5 to 2.5, more preferably in the range of 1.7 to 2.4, and further preferably in the range of 1.8 to 2.2. The specific gravity of the ULMWCNT aggregate can be measured by the method described in JIS Z8807-2012 "Method of measuring density and specific gravity of solids."

[0021] The purity of the ULMWCNT aggregate as MWCNT can be measured by thermogravimetric analysis. For example, a thermogravimetric (TG) curve and a differential thermal analysis (DTA) curve of the ULMWCNT aggregate are obtained using a thermal analyzer (Shimadzu Corporation, DTG-60). The largest exothermic peak in the DTA curve, which has a peak top at about 650°C to 750°C, is the combustion of MWCNT, and the other exothermic peaks are the combustion of substances other than MWCNT. The purity of MWCNT is obtained from the weight loss rate of the TG curve. From the viewpoint of the electrical conductivity of the obtained aggregate, the purity of the ULMWCNT aggregate is preferably 50% by mass or more, more preferably 65% ​​by mass or more, even more preferably 80% by mass or more, and particularly preferably 95% by mass or more.

[0022] ULMWCNT may contain 0.01% by mass to 50% by mass of Fe atoms derived from the iron catalyst used during production. ULMWCNT may contain Fe atoms, for example, in a state where they are adsorbed on the surface of the ULMWCNT, or in a state where they are incorporated inside the fibrous ULMWCNT formed during production. The resulting fibrous ULMWCNTs are preferably flexible and strong. In addition, the conductivity of the ULMWCNT itself is 5000Ω. -1 m -1 More preferably, it is 10,000Ω or more. -1 m -1 More preferably, the electrical conductivity of the ULMWCNT itself is generally 1,000,000 Ω or more. -1 m -1 The following is the result.

[0023] There are no particular limitations on the method for producing the ULMWCNTs contained in the aggregate of the present disclosure. As a method for producing ULMWCNT in the present disclosure, a conventionally known chemical vapor deposition (CVD) method, a method in which a gaseous reactant containing a carbon source is reacted in the presence of a catalyst, or the like can be applied.

[0024] The MWCNTs in the present disclosure can be produced, for example, by referring to the production method described in JP 2016-102047 A. Hereinafter, the method for producing MWCNTs according to the present disclosure will be described with reference to an example, however, the method for producing MWCNTs according to the present disclosure is not limited to the following example.

[0025] An example of a method for producing ULMWCNTs in the present disclosure is the method described in JP 2016-102047 A, i.e., a production method including the steps of passing a gaseous reactant containing one or more carbon sources into a reactor, reacting the one or more gaseous reactants in the presence of a catalyst in a reaction zone of the reactor to form product particles containing carbon, agglomerating the product particles into agglomerates, and applying a force to the agglomerates to continuously move the agglomerates out of the reaction zone (hereinafter also referred to as "production method X"). According to the production method X, MWCNTs, including ULMWCNTs, can be obtained in the form of fibrous aggregates or other aggregate forms that are easy to handle.

[0026] In the manufacturing method X, the force applied to the product particles may be a mechanical force. When the agglomerates include fibrous CNTs, the mechanical force applied to the product particles can be applied by a rotating spindle around which the fibrous CNT-containing agglomerates are wound. In this manner, the fibrous CNTs can be collected as an aggregate on the spindle, or after one or more revolutions around the spindle, the spindle can be continuously unwound and the fibrous CNT aggregates can be accumulated elsewhere.

[0027] The spindle is preferably arranged with the spindle axis perpendicular or parallel to the flow direction of the gaseous reagent or reagents, although the spindle axis may be arranged at other orientations, for example a spindle with the spindle axis arranged at an angle of 25° to the direction of gas flow may also be suitably used to apply a mechanical force to the product particles.

[0028] The spindle can rotate about two axes, for example about two perpendicular axes. In particular, the spindle can rotate about axes perpendicular and parallel to the direction of flow of the gaseous reactants. Such a spindle can pull and twist the aggregates containing fibrous CNTs such that the number and length of twists can be controlled.

[0029] The spindle may be made of metal, ceramic, or plastic. The spindle can have different suitable shapes depending on the characteristics of the material and the intended use of the ULMWCNT aggregate. The spindle can be used as a mold for producing carbon products, for example, by a spin-coating process. The preferred spindle shape is a rod or box shape.

[0030] Fibrous MWCNTs are deposited on a spindle or elsewhere, and the coating thickness and its orientation can be controlled by controlling the reaction time and conditions, or by the conditions under which an electric or other field is applied to the carbon product. The coating thickness and orientation of the carbon product can be controlled, for example, by gas flow forces.

[0031] The spindle rotation speed is preferably between 0.01 rpm (revolutions per minute; hereinafter the same) and 10,000 rpm, more preferably between 0.1 rpm and 100 rpm. The spinning speed, i.e., the rotation speed of the spindle, may be adjusted so that the material is collected at a similar rate as it is produced. The rotation speed may control the thickness of the fibrous ULMWCNT aggregate. In a preferred embodiment, as the spindle rotates, the fibrous ULMWCNT aggregate is processed in the axial direction of the spindle. The processing means that the fibrous ULMWCNT is wound evenly along the spindle, rather than being stacked at only one location on the spindle. The formation of an aggregate by accumulation of fibrous ULMWCNTs may be achieved by other means used in fiber technology.

[0032] The aggregates of fibrous ULMWCNTs may be collected, for example, on the wall of the reactor by a substrate placed in the reactor. The substrate may be a fixed substrate or a rotating guide used to apply a strong and equal force to the ULMWCNTs as they are collected. Suitable substrate configurations for use in fiber technology include a substrate consisting of two guides positioned perpendicular to each other.

[0033] In process X, the mechanical force applied to the product particles may be a force applied by an accelerating gas flow. The accelerating gas flow may be generated by passing the product particles through a reactor having a narrow diameter or through a capillary tube downstream of the reaction zone. A vacuum may be applied to the product particles.

[0034] Other forces that can be applied to the product particles include electrostatic forces, suitably applied by a charged plate. Electrostatic forces require that the product particles be charged. The use of a charged plate allows the MWCNTs to be produced in the form of an intertwined mat on the charged plate.

[0035] Other forces applied to the product particles may also be magnetic forces or photon pressure applied by a light source.

[0036] The CNT source may be injected in the form of a liquid containing a carbon source instead of a gaseous reactant containing a carbon source. When a liquid is used as the CNT source, it can be injected through a single inlet or multiple inlets, for example in a showerhead arrangement.

[0037] The gaseous reactant or reactants are preferably reacted at between 500° C. and 1600° C., more preferably between 1000° C. and 1500° C. or 1600° C. (particularly between 1000° C. and 1500° C.). A temperature gradient is preferably maintained within the reactor, with the reaction zone being maintained at a higher temperature than the product zone of the reactor.

[0038] The gaseous reactants may be mixed with one or more gases that act as diluents. The gaseous reactants may be mixed with gases that do not play a direct role in the reaction but play a supporting role. For example, a gas may be used as a diluent to react with the amorphous carbon by-product, thereby keeping reactive sites on the catalyst intact and available for nanotube production.

[0039] Gases that may be used as diluents include, for example, argon or other inert gases, hydrogen, nitrogen, ammonia, carbon dioxide or helium. Among these, hydrogen is particularly preferable as a gas that can be used as a diluent. The flow rate of the gas as a diluent is preferably 2000 mL (milliliters) / min or less, and more preferably 400 mL / min to 800 mL / min.

[0040] The gas pressure of the gaseous reactants and any diluents is preferably between 0.1 bar and 50 bar, more preferably between 0.5 bar and 5 bar, and even more preferably between 1 bar and 2 bar. In case of gas effluent from the furnace, the effluent gas can be recycled with or without cleaning.

[0041] The agglomerated products can be monitored and the reaction conditions modified according to the information obtained to control the composition of the product, etc. For example, the product can be monitored by online Raman spectroscopy. For carbon nanotubes, data is obtained indicating the single or multi-walled nature of the nanotubes, their diameter, as well as the crystallinity of the nanotubes. The product can also be monitored by online conductivity measurements, gas analysis, monitoring the opacity of the reaction zone and / or monitoring the winding force. The reaction conditions can be modified by an operator or automatically.

[0042] When the agglomerate is removed from the reactor, it is preferable to prevent air from entering the reactor. When the diluent gas contains hydrogen, preventing air from entering the reactor is particularly important, for example, from the viewpoint of preventing an explosive mixture of hydrogen and air from forming in the reactor.

[0043] The product particles in the above production method contain ULMWCNTs, and depending on the production conditions, may contain single-walled carbon nanotubes in addition to multi-walled carbon nanotubes. Fibrous ULMWCNTs may be produced by chemical vapor deposition, where a gaseous reactant, a carbon source, is reacted in the presence of a catalyst.

[0044] Carbon-containing compounds suitable as carbon sources include, for example, carbon monoxide, carbon dioxide, aromatic hydrocarbons (e.g., benzene, toluene, xylene, cumene, ethylbenzene, naphthalene, or mesitylene), non-aromatic hydrocarbons (e.g., methane, ethane, propane, butane, pentane, hexane, cyclohexane, ethylene, propylene, or acetylene), and oxygen-containing hydrocarbons (e.g., formaldehyde, acetaldehyde, acetone, methanol, ethanol, diethyl ether, polyethylene glycol, 1-propanol, ethyl formate, and hydrocarbons including mixtures of two or more thereof). The carbon-containing compound is preferably carbon monoxide, methane, ethylene or acetylene.

[0045] The carbon source preferably contains oxygen. Ethanol is a particularly preferred carbon source. Oxygen can be introduced into the reactor by other methods, such as by using a diluent gas or a carbon source containing water.

[0046] The gaseous reactant that is the carbon source is preferably injected into the reactor at a rate of 0.01 mL / min to 10 mL / min, more preferably 0.08 mL / min to 0.25 mL / min.

[0047] The catalyst is preferably a transition metal group, in particular chromium (Cr), molybdenum (Mo), tungsten (W) or VIIIB transition metal group. Specifically, the catalyst is preferably, for example, iron (Fe), cobalt (Co), nickel (Ni), ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir) and platinum (Pt) or manganese (Mn), or a mixture thereof. Metals from the lanthanide and actinide series (e.g. yttrium (Y)) can also be used as catalyst. Fe, Ni, Co, Mo and mixtures thereof, for example, a mixture of Ni and Co (mass ratio: 50 / 50), a mixture of Fe and Ni, or a mixture of Fe and Mo are more preferred. Any of these transition metals may be used alone or in combination with any of the other transition metals listed to act as a catalyst for CNT growth, with it being particularly preferred that the catalyst is a mixture of two or more of the metals listed.

[0048] The catalyst is preferably formed by decomposition of a precursor. The precursor is preferably a thermally, photo- or plasma-decomposable compound of one or more of the above metals, such as a carbonyl or cyclopentadienyl organometallic compound. Ferrocene, iron pentacarbonyl, nickelocene and cobaltocene are particularly preferred precursors. Suitably, at least 0.01% by weight of the precursor is contained in the carbon source, and preferably 0.2% to 2.5% by weight of the precursor is contained in the carbon source. In one embodiment, 0.23% to 2.3% by weight of the precursor is contained in the carbon source. The catalyst may be used supported on a carrier, and preferred carriers include silica and magnesium oxide.

[0049] The carbon source is preferably reacted in the presence of a promoter. Suitable promoters are one or more of sulfur, phosphorus, molybdenum and organic compounds of these elements. Thiophene is also one of the preferred promoters. Suitably, up to 10% by weight (10% by weight or less) of the promoter is included in the carbon source. Preferably, 0.2% to 6% by weight of the promoter is included in the carbon source. When high or low concentrations of thiophene are used as the promoter, MWCNTs are formed. For example, MWCNTs are well formed using ethanol containing 0 mass % or 1.5 mass % to 4.0 mass % thiophene and 1.0 mass % to 10.0 mass % (particularly 2.3 mass %) ferrocene, with an injection rate of 5.0 mL / hour to 30.0 mL / hour (particularly 7.5 mL / hour), a hydrogen flow rate of 400 mL / min to 800 mL / min, and a synthesis temperature of 1100°C to 1180°C.

[0050] According to the production method X, it is possible to obtain fibrous CNTs having a length of at least 500 μm, for example, at least 1 mm. The fibrous CNTs can take the form of a thread or a mat. The length of the fibrous CNTs can be controlled, for example, by the winding capacity of a spindle used in producing the fibrous CNTs.

[0051] The manufacturing method X preferably includes a step of reacting a carbon source in a reaction region of a reactor to generate CNTs, and a step of aggregating the CNTs into aggregates by applying a force to the CNTs. According to this manufacturing method, a fibrous CNT aggregate can be easily manufactured.

[0052] In another embodiment, a procedure may be taken that includes generating ULMWCNTs in a reaction zone by the methods described above, condensing the ULMWCNTs to form the aggregates, and continuously withdrawing the aggregates from near the reaction zone. In another embodiment, the method may include generating ULMWCNTs in a reaction region, continuously electrostatically attracting the ULMWCNTs from the reaction region, and recovering the ULMWCNTs as the aggregate.

[0053] The above manufacturing method X is just one example, and the manufacturing method of MWCNTs, including ULMWCNTs, is not limited to the above.

[0054] [Fe atom] The aggregate according to the present disclosure contains Fe atoms, and the content ratio of Fe atoms relative to the total mass of the aggregate is equal to or greater than 0.5 mass % and less than 10 mass %. ULMWCNT contains carbon and is expected to be electrically conductive, but when ULMWCNT is produced in the presence of a catalyst containing metal atoms such as Fe, there is concern that Fe atoms from the catalyst will be included in the ULMWCNT, reducing its electrical conductivity. Therefore, traditionally, after production of ULMWCNT, the ULMWCNT has been washed with acid to remove Fe atoms and other metal atoms. However, according to the investigations of the present inventors, it was found that in the case of including ULMWCNTs with a maximum length of 1000 μm to 30000 μm, when the maximum length of the CNTs is within the above range and the content ratio of Fe atoms to the total mass of the aggregate is 0.5 mass % or more and less than 10 mass %, the electrical conductivity of the aggregate is maintained while the dispersibility in the dispersion medium is further improved.

[0055] The content ratio of Fe atoms relative to the total mass of the aggregate of the present disclosure is equal to or greater than 0.5 mass% and less than 10 mass%, preferably greater than 1.0 mass% and less than 10 mass%, more preferably 1.2 mass% to 9.5 mass%, even more preferably 1.5 mass% to 9 mass%, particularly preferably 2 mass% to 8 mass%, and especially preferably 3 mass% to 7 mass%.

[0056] The content ratio of Fe atoms to the total mass of the aggregate can be measured, for example, by the following method. The aggregate of the present disclosure is completely dissolved in an acid such as hydrochloric acid or nitric acid. In order to completely dissolve the aggregate of the present disclosure in an acid, a pretreatment such as dry ashing, wet ashing, or melting treatment may be performed. The content ratio of Fe atoms can be measured by performing inductively coupled plasma atomic emission spectroscopy (ICP-AES) or inductively coupled plasma mass spectrometry (ICP-MS) on the solution in which the aggregate of the present disclosure is completely dissolved in an acid. ICP-MS is preferably performed because it can be measured with higher sensitivity.

[0057] As described above, ULMWCNT may contain 0.01% by mass to 50% by mass of Fe atoms derived from iron, which is a catalyst used during production. ULMWCNT may contain Fe atoms, for example, in a state where they are adsorbed on the surface of the ULMWCNT, or in a state where they are incorporated inside the fibrous ULMWCNT formed during production. That is, in the present disclosure, the Fe atoms contained in the aggregate may include Fe atoms derived from the catalyst used in the production of multi-walled carbon nanotubes. In the aggregate of the present disclosure, taking into consideration the content of catalyst-derived Fe atoms contained in the ULMWCNT, it is preferable to adjust the content ratio of Fe atoms to the total mass of the aggregate to a desired content ratio within a range of 0.5 mass% or more and less than 10 mass%. Note that, needless to say, when the content ratio of catalyst-derived Fe atoms to the total mass of the aggregate is the desired content ratio, there is no need to take any particular measure to adjust the content ratio of Fe atoms.

[0058] When the content ratio of Fe atoms to the total mass of the aggregate is 10 mass % or more, the content ratio of Fe atoms to the total mass of the aggregate can be adjusted to less than 10 mass % by a known method, for example, by washing the aggregate with water, acid, or an acid aqueous solution (for example, a 1 mass % to 37 mass % aqueous solution of hydrochloric acid, particularly a 35 mass % aqueous solution) to wash and remove some of the Fe atoms. If the content ratio of Fe atoms to the total mass of the aggregate is less than 0.5 mass%, the content ratio of Fe atoms to the total mass of the aggregate can be adjusted to 0.5 mass% or more by immersing the aggregate in an aqueous solution of 1 mass% to 46 mass% (particularly, about 5 mass%) iron nitrate or 1 mass% to 47 mass% (particularly, about 40 mass%) iron chloride as a source of Fe atoms to adsorb Fe atoms to the surface of the fibrous ULMWCNT.

[0059] The mechanism of action of the improved electrical conductivity and dispersibility in the aggregate of the present disclosure is not clear, but is believed to be as follows: However, the following speculation is not intended to limit the interpretation of the aggregate of the present disclosure, but is provided as an example. When Fe atoms are contained in known short CNTs, the presence of Fe atoms narrows the contact points between the CNTs, making it difficult to form conductive paths, resulting in a problem of reduced conductivity.

[0060] The ULMWCNTs contained in the aggregate of the present disclosure have a maximum length in the range of 1000 μm to 30000 μm, so that the contact points between them are wide, and aggregation is likely to occur. Here, when an appropriate amount of Fe atoms are attached to the surface of the ULMWCNT, it is considered that the Fe atoms contained in the aggregate moderately inhibit the contact between multiple ULMWCNTs by the Fe atoms, thereby suppressing aggregation and improving dispersibility. When aggregation of ULMWCNTs is suppressed, the electrical conductivity generally decreases, but since the ULMWCNTs contained in the aggregate of the present disclosure have a maximum length in the range of 1000 μm to 30000 μm, a sufficient contact area is secured even if aggregation is suppressed due to the presence of Fe atoms, and it is considered that both improved dispersibility and good electrical conductivity are achieved. In ULMWCNTs with an Fe atom content of 10% by mass or more, the presence of Fe atoms narrows the contact points between the ULMWCNTs, making it difficult to connect conductive paths and reducing conductivity. In ULMWCNTs with an Fe atom content of less than 0.5% by mass, the presence of Fe atoms does not suppress aggregation, and the contact points become wider, resulting in good conductivity but reduced dispersibility.

[0061] When the content of Fe atoms relative to the total mass of the aggregate of the present disclosure is within the above range, the specific gravity of the ULMWCNT aggregate increases slightly due to the presence of Fe atoms. For example, when the content of Fe atoms in the aggregate is 5 mass %, the specific gravity is about 2.2. When the aggregate of the present disclosure is used as a conductive assistant described below, since the carbon material in the electrode, graphite, has a specific gravity of 2.2 and Ketjen black, has a specific gravity of 2.7, the specific gravity of the aggregate is increased by the Fe atoms, thereby reducing the difference in specific gravity with the carbon material, and thus providing the additional effect of improving dispersibility in the carbon material. The method for measuring the specific gravity of the aggregate is as described in the section on multi-walled carbon nanotubes.

[0062] <Multi-walled carbon nanotube aggregate: Second embodiment> A second embodiment of the multi-walled carbon nanotube aggregate of the present disclosure includes a multi-walled carbon nanotube aggregate including multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and Fe atoms, the content ratio of Fe atoms relative to the total mass of the aggregate being 0.5 mass% or more and less than 10 mass%.

[0063] A second embodiment of the multi-walled carbon nanotube aggregate of the present disclosure is an aggregate of multi-walled carbon nanotubes including multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and Fe atoms, the content ratio of Fe atoms relative to the total mass of the aggregate being 0.5 mass% or more and less than 10 mass%.

[0064] In this disclosure, "tensile strength" is measured with reference to the tensile test set forth in standard ISO 527-1. The tensile strength of the multi-walled carbon nanotube according to the second embodiment of the present disclosure indicates a value measured in a tensile state such as a sheet or fiber. When the multi-walled carbon nanotube aggregate is in the form of a sheet, the sheet-like aggregate is cut into a piece of 75 mm x 10 mm to be used as the measurement sample, which is then fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AGS-X Series) and subjected to a tensile test at a speed of 1 mm / min. The breaking strength at which the measurement sample breaks is taken as the tensile strength. When the multi-walled carbon nanotube is in a thread form, the fiber-like multi-walled carbon nanotube is cut to a length of 500 mm and used as the measurement sample. This is fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AGS-X Series) and a tensile test is performed at a speed of 1 mm / min using a fine wire gripper (Shimadzu Corporation). The breaking strength at which the measurement sample breaks is taken as the tensile strength. When the sheet-like measurement sample does not satisfy the above-mentioned size, or when the thread-like measurement sample does not satisfy the above-mentioned length, the measurement sample is used as it is to measure the tensile strength.

[0065] The tensile strength of the multi-walled carbon nanotube according to the present disclosure is preferably 10 MPa to 100 MPa, more preferably 30 MPa to 85 MPa, and even more preferably 50 MPa to 70 MPa. When the tensile strength of the multi-walled carbon nanotube is 50 MPa or more, the maximum length of the multi-walled carbon nanotube is sufficient, so that the electrical conductivity of the multi-walled carbon nanotube is easily ensured. When the tensile strength of the multi-walled carbon nanotube is 70 MPa or less, the force required for pulverizing the sheet-like or fibrous multi-walled carbon nanotube as required is small, so that the pulverization process, which is a post-processing process performed as required, can be easily performed.

[0066] The multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa according to the present disclosure may be pulverized as required by, for example, a freeze-pulverization method. The freeze-pulverization method is a processing method in which, whether the multi-walled carbon nanotubes are in the form of a sheet or fiber, the multi-walled carbon nanotubes are quenched with liquid nitrogen to eliminate the elasticity of the multi-walled carbon nanotubes and facilitate pulverization. Alternatively, pulverization may be performed by a known pulverization method such as a ball mill.

[0067] The aggregate of multi-walled carbon nanotubes contains Fe atoms, and the content ratio of Fe atoms to the total mass of the aggregate is 0.5 mass % or more and less than 10 mass %. In a second embodiment of the aggregate of the present disclosure, the content ratio of Fe atoms to the total mass is equal to or greater than 0.5 mass% and less than 10 mass%, preferably greater than 1.0 mass% and less than 10 mass%, more preferably 1.2 mass% to 9.5 mass%, even more preferably 1.5 mass% to 9 mass%, particularly preferably 2 mass% to 8 mass%, and especially preferably 3 mass% to 7 mass%. Unless otherwise specified, "the assembly of the present disclosure" refers to the assembly of the first embodiment of the present disclosure.

[0068] <Method of manufacturing the assembly according to the present disclosure> The aggregate of the present disclosure can be obtained by adjusting the Fe atom content ratio to the total mass of the aggregate containing ULMWCNTs obtained by the above-mentioned manufacturing method to a range of 0.5 mass % or more and less than 10 mass %. The method for adjusting the Fe atom content ratio is as described above. First, the content ratio of Fe atoms resulting from the reaction catalyst in the aggregate containing ULMWCNT is measured, and then the content ratio is taken into consideration and either Fe atoms are removed or further adsorbed to adjust the content ratio of Fe atoms. If the content ratio of Fe atoms in the aggregate containing ULMWCNT is within the range of the target value, there is no particular need to adjust the content ratio of Fe atoms.

[0069] <Physical properties of the assembly according to the present disclosure> 1.Rsp value The assembly of the present disclosure preferably has an Rsp value with respect to the dispersion medium of 300 to 10,000, more preferably 500 to 7,000, further preferably 1,000 to 5,000, and particularly preferably 3,500 to 4,500. The Rsp value is a measure of affinity for a dispersion medium, and can be measured by a pulsed nuclear magnetic resonance (pulsed NMR) method. The pulsed NMR method can measure the affinity of a dispersion such as the aggregate of the present disclosure for a dispersion medium because it can measure the dispersion liquid without diluting it and does not approximate the shape of the dispersoid to a spherical shape. When the Rsp value of the aggregate of the present disclosure for the dispersion medium is within an appropriate range, it can be determined that the dispersibility of the aggregate of the present disclosure for the dispersion medium is good. The Rsp value is the relaxation time T measured by a pulse NMR device after placing the dispersion in a sample tube. 2s and the relaxation time T measured by putting only the dispersion medium in the test tube. 2b By comparing with the above, it can be calculated using the following formula. Rsp=(T 2b / T 2s )-1

[0070] 2.Viscosity As described above, the aggregate of the present disclosure has a high affinity for the dispersion medium, and therefore the viscosity of the dispersion tends to be low. When the viscosity of the dispersion is within an appropriate range, it can be determined that the dispersibility of the aggregate of the present disclosure in the dispersion medium is good. The shear rate of the dispersion is 1s -1 When the shear rate of the dispersion is 100 s, the viscosity is preferably 0.1 Pa·s to 4.8 Pa·s, more preferably 0.5 Pa·s to 4.5 Pa·s, and further preferably 1.0 Pa·s to 4.2 Pa·s. -1 In this case, the viscosity is preferably from 0.001 Pa·s to 0.11 Pa·s, more preferably from 0.005 Pa·s to 0.1 Pa·s, and further preferably from 0.01 Pa·s to 0.09 Pa·s. The viscosity at each shear rate can be obtained by rheometer measurement. For example, the shear rate dependency of viscosity can be evaluated using a viscoelasticity measuring device (Anton Paar, MCR302) under the following measurement conditions. Measuring tool: Corn plate Measurement mode: Rotation mode Shearing rate: 0.01s -1 ~1000s -1 Temperature: 25℃ From the data obtained, the viscosities are read off at the following shear rates: Shear rate=1s -1 Shear rate=100s -1

[0071] 3. Conductivity The assembly of the present disclosure has good electrical conductivity because the main component is carbon. The electrical conductivity of the assembly of the present disclosure can be determined from the volume resistivity. When the volume resistivity measured under the following conditions is lower than a predetermined value, the polymer of the present disclosure can be determined to have good electrical conductivity. The electrical conductivity of the assembly of the present disclosure, calculated from the volume resistivity, is 1.5 × 10 -2 It is preferable that the resistance is Ω·cm or less, and 1.0×10 -5 Ω cm~1.2×10 -2 Ω cm is more preferable, and 5.0×10 -5 Ω cm~1.0×10 -2 More preferably, it is 1.0×10 -4 Ω cm~9.9×10 -3 It is particularly preferred that the resistivity is Ω·cm.

[0072] The volume resistivity of the assembly of the present disclosure is measured by a four-probe method using a resistivity meter at 25° C. A Loresta device can be used as the resistivity meter. Specifically, using a Loresta device (product name: powder resistivity measurement system MCP-PD51, low resistivity meter Loresta-GP, low resistivity probe for powder MCP-PD511 (constant current application type 4-probe method), all manufactured by Nitto Seiko Analytech Co., Ltd.), the multi-walled carbon nanotube aggregate is introduced into the powder resistivity measurement probe unit, and pressed with 5 kN using the attached hydraulic pump. After the target load is reached, the volume resistivity (Ω cm) is measured. When the aggregate needs to be pulverized in order to measure the volume resistivity of the aggregate of the present disclosure, for example, the freeze-pulverization method can be used as described above. In addition, pulverization may be performed by a known pulverization method such as a ball mill.

[0073] The volume resistivity of the assembly of the present disclosure can also be calculated from the surface resistivity measured by the following method. The surface resistance of the ULMWCNT aggregate is measured using a resistivity test by the four-probe method according to JIS K 7149-1994 using a Loresta EP MCP-T360 (manufactured by Dia Instruments Co., Ltd.). The volume resistivity is calculated by multiplying the surface resistance value obtained by the four-probe method by the film thickness of the aggregate. The conductivity of the aggregate is calculated from the obtained volume resistivity. The film thickness of the assembly of the present disclosure can be measured using a thickness gauge having two circular horizontal plates in accordance with ISO Method A, a thickness measurement method in JIS L 1913-2010 "General nonwoven fabric testing methods."

[0074] [Conductive assistant] As described above, the assembly of the present disclosure has good electrical conductivity, and therefore the assembly of the present disclosure can be used as a conductive assistant (preferably, a conductive assistant for a negative electrode). The conductive assistant has a function of further improving the conductivity of the conductive material by coexisting with the conductive material such as the positive electrode active material and the negative electrode active material. Since the aggregate of the present disclosure contains ULMWCNTs, it has the following properties as an active material serving as a conductive material: In addition to known conductive assistants such as graphite and Ketjen black, the aggregate of the present disclosure can be used as a conductive assistant. As described above, the aggregate of the present disclosure contains Fe atoms at a predetermined content ratio, and therefore the specific gravity of the aggregate of the present disclosure tends to be slightly higher than that of an aggregate of ULMWCNTs, which generally has a specific gravity in the range of 1.8 to 2.0. For example, when the content ratio of Fe atoms in the aggregate is 5 mass %, the specific gravity of the aggregate is about 2.2, which is smaller than the difference in specific gravity between the carbonaceous materials used as conductive assistants, such as graphite (specific gravity 2.2) and Ketjen black (specific gravity 2.7). In addition to the inherent dispersibility in the dispersion medium that the aggregate of the present disclosure has, the aggregate also has better dispersibility in the carbonaceous material used in combination.

[0075] An example of the use as a conductive assistant may be, for example, when manufacturing a positive electrode of a battery, a positive electrode active material, the conductive assistant which is the aggregate of the present disclosure, and a binder are mixed in a predetermined mass ratio, a solvent is added to the mixture to prepare a slurry, which is applied onto a current collector for a positive electrode, dried, and stretched to produce a positive electrode.

[0076] Another example of the use as a conductive assistant may be, for example, when manufacturing a negative electrode of a battery, a negative electrode active material, the conductive assistant which is the aggregate of the present disclosure, and a binder are mixed in a predetermined mass ratio, a solvent is added to the mixture to prepare a slurry, which is applied onto a current collector for the negative electrode, dried, and stretched to produce a negative electrode.

[0077] Although a combination of a carbon material as a conductive material and the conductive assistant which is an aggregate of the present disclosure has been described above, the use of the conductive assistant of the present disclosure is not limited to the above.

[0078] When the assembly of the present disclosure is used as a conductive assistant, the content ratio can be any ratio relative to the total solid mass of the material including the conductive material and the conductive assistant.

[0079] In addition, the aggregate of the present disclosure may itself be used as a conductive material. The conductive material of the present disclosure includes the aggregate of the present disclosure described above. Applications of the conductive material include use as an electrode material in batteries, for example, lithium ion batteries, specifically as an anode active material, a cathode active material, and the like.

[0080] <Multi-walled carbon nanotube dispersion> The aggregate of the present disclosure has good dispersibility and can therefore be suitably used as a dispersion liquid. The multi-walled carbon nanotube dispersion of the present disclosure (hereinafter, may be simply referred to as the dispersion of the present disclosure) contains the aggregate of the present disclosure described above and a dispersion medium.

[0081] [Dispersion medium] The dispersion medium that may be contained in the dispersion liquid of the present disclosure will be described.

[0082] The dispersion medium preferably contains water, and more preferably contains water as a main component. "Containing water as a main component" means that the proportion of water in the dispersion medium is more than 50% by mass. The proportion of water in the dispersion medium is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more, and may be, for example, 100% by mass. The water is not particularly limited, but is preferably distilled water, ion-exchanged water, pure water, or the like, which contains fewer impurities.

[0083] The dispersion medium may be a mixture of water and a hydrophilic solvent. Examples of hydrophilic solvents include carbonate compounds such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and butylene carbonate; ether compounds such as tetrahydrofuran; ketone compounds such as acetone; lower alcohol compounds such as methanol and ethanol; and acetonitrile. When the dispersion medium contains a hydrophilic solvent, the proportion of the hydrophilic solvent in the dispersion medium is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.

[0084] In addition to the aggregates and dispersion medium of the present disclosure, the dispersion of the present disclosure may further include other components that may be used in the dispersion. Examples of other components include dispersants, antifoaming agents, antistatic agents, CNTs other than the ULMWCNTs according to the present disclosure, carbon materials other than CNTs, etc. Also, it may further contain trace amounts of impurity components, so-called unavoidable impurities, etc.

[0085] [Dispersant] The dispersion of the present disclosure may contain a dispersant for the purpose of further improving the dispersibility and dispersion stability of the aggregate of the present disclosure. The dispersant is not particularly limited, and examples thereof include various surfactants. Examples of the dispersant also include polymer compounds such as resins. The dispersant is preferably a surfactant. The surfactant may be an ionic surfactant or a nonionic surfactant, and is not particularly limited. The surfactants can be used alone or in combination of two or more.

[0086] Examples of ionic surfactants include anionic surfactants, cationic surfactants, and amphoteric surfactants. Examples of the anionic surfactant include aromatic sulfonic acid surfactants such as alkylbenzene sulfonates (e.g., dodecylbenzene sulfonate) and dodecylphenyl ether sulfonate; ether sulfate surfactants; phosphate surfactants; and carboxylic acid surfactants. Examples of the cationic surfactant include alkylamine salts and quaternary ammonium salts. Examples of the amphoteric surfactant include alkyl betaine surfactants and amine oxide surfactants. As the ionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic ionic surfactant) is preferred, and aromatic sulfonic acid surfactants such as alkylbenzene sulfonate and dodecyl phenyl ether sulfonate are more preferred. Aromatic ionic surfactants tend to be excellent in dispersibility, dispersion stabilization, and concentration of aggregates of multi-walled carbon nanotubes.

[0087] Examples of nonionic surfactants include sugar ester surfactants such as sorbitan fatty acid esters and polyoxyethylene sorbitan fatty acid esters; fatty acid ester surfactants such as polyoxyethylene resin acid esters and polyoxyethylene fatty acid diethyl esters; ether surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers and polyoxyethylene polypropylene glycols; polyoxyalkylene octyl phenyl ethers, polyoxyalkylene nonyl phenyl ethers, polyoxyalkyl dibutyl phenyl ethers, polyoxyalkyl styryl phenyl ethers, polyoxyalkyl benzyl phenyl ethers, polyoxyalkyl bisphenyl ethers, polyoxyalkyl cumyl phenyl ethers and polyoxyalkylene phenyl ethers. Examples of the surfactant include aromatic nonionic surfactants. As the nonionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic nonionic surfactant) is preferable, polyoxyalkylene phenyl ether is more preferable, and polyoxyethylene phenyl ether is further preferable. Aromatic nonionic surfactants tend to be excellent in dispersibility, dispersion stabilization, and concentration of aggregates of multi-walled carbon nanotubes.

[0088] Other dispersants that are excellent in dispersing ability, dispersion stabilizing ability, and high concentration of multi-walled carbon nanotube aggregates include DEMOL (registered trademark: the same applies below) N, DEMOL RN, and DEMOL T (manufactured by Kao Corporation), which are sodium salts of β-naphthalenesulfonic acid formalin condensates; Brij S 100 (Sigma-Aldrich), polyvinylpyrrolidone K30 (e.g., Fujifilm Wako Pure Chemical Industries, Ltd.), carboxymethylcellulose (CMC) (e.g., Daicel Miraizu Co., Ltd.), sodium deoxycholate (e.g., Fujifilm Wako Pure Chemical Industries, Ltd.), SOLSPERSE TM W100, SOLSPERSE TM W150 (manufactured by Lubrizol Japan, Ltd.) is exemplified. From the viewpoint of excellent dispersibility, dispersion stabilizing ability and high concentration of the aggregate of multi-walled carbon nanotubes, CMC is particularly preferable.

[0089] When the dispersion liquid of the present disclosure contains a dispersant, the amount of the dispersant used is not particularly limited and can be appropriately set depending on the type of dispersant, the amount of the aggregate of multi-walled carbon nanotubes, the amount of the dispersion medium, and the like.

[0090] [Method for producing dispersion] The method for producing the dispersion of the present disclosure is not particularly limited. The dispersion according to the present disclosure can be produced by dispersing the aggregate according to the present disclosure in a dispersion medium. That is, the dispersion according to the present disclosure can be produced by a method including a step of dispersing the aggregate of multi-walled carbon nanotubes according to the present disclosure in a dispersion medium (also referred to as a "dispersion step"). The dispersion medium that can be used in the dispersion step is as described above.

[0091] The dispersion method is not particularly limited. Examples of the dispersion method include methods using a dispersion device such as a stirrer, a homogenizer, a colloid mill, a flow jet mixer, a dissolver, a paint conditioner, a Manton emulsifier, a jet mill, or an ultrasonic device. Examples of the dispersion method include methods using known pulverization means, such as ball milling (e.g., ball mill, vibration ball mill, planetary ball mill, bead mill, etc.), sand milling, colloid milling, jet milling, roller milling, and dispersing machines such as vertical or horizontal agitator mills, attritors, colloid mills, three-roll mills, pearl mills, super mills, impellers, dispersers, KD mills, dynatrons, and pressure kneaders. As a dispersion method, a method using a jet mill is preferable, and a method using a wet jet mill is more preferable. A wet jet mill is a dispersing device that pressure-feeds a mixture in a solvent as a high-speed flow from a nozzle arranged in a sealed pressure-resistant container. In the wet jet mill, the aggregates of multi-walled carbon nanotubes are dispersed by collisions between opposing flows in a pressure-resistant container, collisions with the container wall, turbulence caused by the high-speed flow, shear flow, and the like. As the wet jet mill, an ultra-high pressure homogenizer (model number: NAGS20, NAGS100, NAGS200, NAGS1000, etc.) manufactured by Jokou Co., Ltd. can be suitably used. However, the wet jet mill is not limited to this. When the above-mentioned ultra-high pressure homogenizer is used as the dispersing device, the dispersion treatment pressure is preferably 10 MPa to 250 MPa.

[0092] The method for producing the dispersion of the present disclosure includes, before the dispersion step, a step of drying the aggregate of the present disclosure. (also referred to as a "drying step"). When moisture is attached to the multi-walled carbon nanotubes, the multi-walled carbon nanotubes tend to adhere to each other due to the surface tension of the water, which may lead to a decrease in dispersibility. Therefore, by performing a drying process for the aggregate before the dispersion process, moisture attached to the ULMWCNT surfaces and the like contained in the aggregate is removed, and adhesion between ULMWCNTs due to moisture attachment is suppressed, thereby further improving the dispersibility of the aggregate of the present disclosure in the dispersion medium. The drying method is not particularly limited. Examples of the drying method include heat drying, vacuum drying, and heat vacuum drying. The drying method is preferably heated vacuum drying. The drying temperature is not particularly limited, and is preferably from 40°C to 100°C, for example. The drying time is not particularly limited and can be set appropriately depending on the drying temperature, the degree of moisture adhering to the assembly of the present disclosure, and the like.

[0093] [Application of dispersion liquid] The dispersion of the present disclosure has good dispersibility in the dispersion medium of the aggregate of the present disclosure and has excellent electrical conductivity, and therefore can be used for various applications. The dispersion liquid can be used for conductive inks, antistatic agents, conductive materials for forming circuit patterns, transparent electrode materials, water-soluble polymer fillers, etc., and is preferably used as a conductive ink. The dispersion of the present disclosure is preferably applied to an ink composition for forming a lithium battery negative electrode, among other conductive inks. By using the dispersion liquid of the present disclosure as an ink composition for forming a lithium battery negative electrode, a lithium battery negative electrode having good electrical conductivity can be easily produced.

[0094] When the dispersion liquid of the present disclosure is applied to a conductive ink, the ink can be produced in the same manner as the dispersion liquid of the present disclosure, except that the ink further contains a viscosity modifier, an antioxidant, etc., which are components of the conductive ink.

[0095] One application of the assembly of the present disclosure is an electrode or a secondary battery that contains the assembly of the present disclosure as a conductive assistant. An electrode containing the conductive wire assistant according to the present disclosure has excellent conductive path formation properties within the electrode, and therefore a secondary battery containing the electrode has excellent cycle characteristics. The electrode may include the conductive assistant according to the present disclosure. The conductive assistant included in the electrode is the same as the conductive assistant according to the present disclosure, and therefore, hereinafter, a description of the conductive assistant will be omitted. The electrode may be at least one of a positive electrode and a negative electrode. The electrode may include an electrode active material layer.The electrode may include a current collector and an electrode active material layer disposed on the current collector.

[0096] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector.

[0097] The electrode active material layer can include an electrode active material. The electrode active material is preferably electrode active material particles.

[0098] When the electrode is a positive electrode, the electrode active material particles are not particularly limited and may include a positive electrode active material that is commonly used as a positive electrode material. Specifically, the positive electrode active material may be, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), etc. Layered compounds, substituted with one or more transition metals; Lithium iron oxides such as LiFe3O4; Chemical formula Li 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.66); 2-c3 M c3O2 (where M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01 ≦ c3 ≦ 0.1), or a lithium manganese composite oxide represented by Li2Mn3MO8 (where M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); examples include LiMn2O4 in which a part of Li in the chemical formula is substituted with an alkaline earth metal ion.

[0099] When the electrode is a negative electrode, the electrode active material is not particularly limited and can include a negative electrode active material commonly used for negative electrode materials. Specifically, the negative electrode active material can include graphite-based active material particles or silicon-based active material particles. As the graphite-based active material particles, one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized mesocarbon microbeads may be used. By using artificial graphite, the rate performance can be improved.

[0100] As the silicon-based active material particles, one or more selected from the group consisting of Si, SiOx (0 < x < 2), Si-C composite, and Si-Y alloy (where Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a transition metal, a Group 13 element, a Group 14 element, a rare earth element, and combinations thereof) may be used. By using the silicon-based active material particles, the battery can be made to have a higher capacity.

[0101] The electrode active material layer can further include a binder. The binder is not particularly limited and may include binders that are commonly used in electrode materials. Examples of the binder include at least one polymer selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and polyacrylic acid, as well as polymers in which hydrogen atoms of these polymers are substituted with Li, Na, Ca, or the like.

[0102] <Secondary battery> The secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. At least one of the positive electrode and the negative electrode is preferably an electrode according to the present disclosure, and the negative electrode is preferably an electrode according to the present disclosure.

[0103] The separator separates the negative electrode and the positive electrode and provides a path for lithium ion migration, and is not particularly limited as long as it is a separator that is usually used as a separator in a secondary battery. The separator preferably has low resistance to ion migration of the electrolyte and is excellent in the ability to wet the electrolyte solution. Specific examples of the separator include porous polymer films. The porous polymer film may be a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminated structure in which two or more of these films are laminated. The separator may be a normal porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber, polyethylene terephthalate fiber, etc. In order to ensure heat resistance or mechanical strength, the separator may be coated with a ceramic component or a polymeric substance. The separator may have a single-layer or multi-layer structure.

[0104] Examples of the electrolyte include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium ion secondary batteries.

[0105] Specifically, the electrolyte can include a non-aqueous organic solvent and a metal salt. Examples of non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0106] Among carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents with high dielectric constants and good dissociation of lithium salts, and therefore can be preferably used as non-aqueous organic solvents. It is more preferable to use such cyclic carbonates as non-aqueous organic solvents by mixing them with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, since this makes it possible to obtain an electrolyte having high electrical conductivity.

[0107] The metal salt may be a lithium salt. The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. The anion portion of the lithium salt is, for example, F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more types selected from the group consisting of:

[0108] In addition to the nonaqueous organic solvent and metal salt that are the constituents of the electrolyte, the electrolyte may further contain one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, and the like.

[0109] The above-mentioned secondary battery can be configured into a battery module including the secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0110] <Planar aggregate> The planar aggregate of the present disclosure includes the multi-walled carbon nanotube aggregate of the present disclosure. The content of the multi-walled carbon nanotube aggregate of the present disclosure contained in the planar aggregate of the present disclosure is usually 1 mass% or more with respect to the total mass of the planar aggregate. The planar aggregate of the present disclosure may include other components such as a carbon nanotube aggregate having a maximum length of less than 1000 μm, particularly a multi-walled carbon nanotube aggregate having a maximum length of less than 1000 μm.

[0111] [Method of producing planar assembly] The method for producing the planar assembly according to the present disclosure is not particularly limited. The planar aggregate of the present disclosure can be produced, for example, as a nonwoven fabric-like planar aggregate, by dispersing the multi-walled carbon nanotube aggregate of the present disclosure, or the multi-walled carbon nanotube aggregate of the present disclosure and other components such as a carbon nanotube aggregate having a maximum length of less than 1000 μm, particularly a multi-walled carbon nanotube aggregate having a maximum length of less than 1000 μm, in water or other fluid, and filtering once or twice or more times.

[0112] Certain embodiments of the planar assembly of the present disclosure include, for example, a film.

[0113] The planar assemblies of the present disclosure are useful, for example, in filters, electromagnetic shields, and extreme ultraviolet (EUV) pellicles. EXAMPLES

[0114] The aggregate and the dispersion containing the aggregate of the present disclosure will be described in more detail below with reference to the following examples. The aggregate and the dispersion of the present disclosure are not limited to the following examples as long as they do not deviate from the gist of the disclosure. Unless otherwise specified, "%" means "% by mass".

[0115] Example 1 1. Preparation of sheet-shaped ULMWCNT aggregate 1 Sheet-like ULMWCNT aggregate 1 was prepared by a floating catalyst method (CVD method) that directly interacts with the self-assembly of CNT bundles in the gas phase. First, ferrocene as a metal catalyst precursor containing Fe atoms and thiophene as a promoter were introduced into a continuous flow of carrier gas in a once-through reactor whose temperature was controlled at 400°C to 700°C. A mixture of nitrogen and argon was used as the carrier gas. The flow rate of the carrier gas was 30,000sccm (standard cubic centimeter per minute). By maintaining the temperature in the flow-through reactor within the above range, the metal catalyst precursor was produced as a particulate metal catalyst. The region in which the metal catalyst was produced is referred to as the first temperature zone.

[0116] The carbon source, methane, was then released into the carrier gas stream. The metal catalyst and carbon source were fed into a second temperature zone downstream of the first temperature zone, which was temperature-controlled at 1400° C. The second temperature zone was maintained at a temperature sufficient to produce carbon nanotube aggregates.

[0117] In the second temperature zone, an electric field was generated within the temperature-controlled flow reactor, which generated aggregates of ULMWCNTs. The ULMWCNT aggregates were continuously discharged through the outlet of a flow-type reactor whose temperature was controlled at 100°C to 500°C, and the sheet-like ULMWCNT aggregates were collected by continuous discharge. The obtained sheet-like ULMWCNT aggregate contains ULMWCNT and MWCNT. The obtained sheet-like ULMWCNT aggregate was washed with deionized water for 10 seconds in order to adjust the content ratio of Fe atoms, and a sheet-like ULMWCNT aggregate 1 was obtained.

[0118] 2. Preparation of Dispersion 1 The following materials were mixed and pre-dispersed by processing for 1 hour with an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. to obtain a pre-dispersion liquid 1. Note that the sheet-like ULMWCNT aggregate 1 was cut into small pieces of about 1 cm x 1 cm with scissors before mixing so that the sheet-like ULMWCNT aggregate 1 would not get tangled in the blades of the homogenizer. (Dispersion liquid composition) 1.1g of the sheet-like ULMWCNT aggregate 1 obtained above ·CARBOXYMETHYL CELLULOSE SODIUM SALT HIGH VISCOSITY (manufactured by MP Biomedicals) 1.65g ·Pure water 547.2g The above pre-dispersion liquid 1 was subjected to main dispersion using an ultra-high pressure homogenizer (model: NAGS100) manufactured by Joko Corporation as a wet jet mill, and thus dispersion liquid 1 was obtained. Nozzle diameter: 0.22mm Pressure: 85MPa Number of times: 8 Method: Circulation method

[0119] 3. Evaluation 3-1. Content of ULMWCNTs with a maximum length of 1000μm to 30000μm First, when 100 MWCNTs were observed in multiple adjacent SEM photographs (magnification: 5000x) of the sheet-like ULMWCNT aggregate 1 of Example 1 obtained above, the content ratio of ULMWCNTs with a maximum length of 1000 μm to 30000 μm was 75%, and the maximum value of the maximum length of the 100 observed MWCNTs was 3500 μm.

[0120] 3-2. Ratio of Fe atoms to the total mass of the aggregate An inductively coupled plasma mass spectrometry (ICP-MS) device (PerkinElmer, NexION 2000C) was used to measure the content ratio of Fe atoms contained in the sheet-like ULMWCNT aggregate 1 of Example 1. The sheet-like ULMWCNT aggregate 1 was subjected to low-temperature ashing / acid dissolution as a pretreatment, and measured with the above device. As a result, the content ratio of Fe atoms to the total mass of the aggregate in the sheet-like ULMWCNT aggregate 1 of Example 1 was 5.6 mass%.

[0121] 3-3.Rsp value The sheet-like ULMWCNT aggregate 1 of Example 1 was dispersed in the above-mentioned method to obtain a dispersion liquid 1, which was then placed in a sample tube. The relaxation time T 2s was measured. In addition, pure water is placed in the sample tube, and the relaxation time T 2b The Rsp value was calculated using the following formula: I put it out. Rsp=(T 2b / T 2s )-1 The results are shown in Table 1.

[0122] 3-4.Viscosity The viscosity of Dispersion 1 was obtained by rheometer measurement. Using a viscoelasticity measuring device (Anton Paar, MCR302), the shear rate dependency of viscosity was evaluated under the following conditions. Measuring tool: Corn plate Measurement mode: Rotation mode Shearing rate: 0.01s -1 ~1000s -1 Temperature: 25℃ From the data obtained, the viscosities were read at the following shear rates: Shear rate=1s -1 Shear rate=100s -1 The results are shown in Table 1.

[0123] 3-5.Volume resistivity The sheet-like ULMWCNT aggregate 1 of Example 1 was pulverized by a freeze-pulverization method. Using a Loresta device (product name: powder resistivity measurement system MCP-PD51, low resistivity meter Loresta-GP, low resistance probe for powder MCP-PD511 (constant current application type 4-probe method), all manufactured by Nitto Seiko Analytech Co., Ltd.), the pulverized sheet-like ULMWCNT aggregate 1 was introduced into a powder resistivity measurement probe unit, and pressed at 5 kN using an attached hydraulic pump until the target load was reached, and then the volume resistivity (Ω·cm) was measured. As a result, the volume resistivity is 9.2 × 10 at 5 kN. -3 The value was Ω·cm.

[0124] Tensile strength The sheet-like ULMWCNT aggregate 1 of Example 1 was cut into a size of 5 mm x 100 mm to be used as a measurement sample, which was fixed to the gripping portion of a tensile tester (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. As a result, the tensile strength was 11.3 MPa.

[0125] Example 2 1. Preparation of Fibrous ULMWCNT Assembly 2

[0126] Like the sheet-like ULMWCNT aggregate 1, the fibrous ULMWCNT aggregate 2 was also produced by the floating catalyst method (CVD method) which directly interacts with the self-assembly of CNT bundles in the gas phase. First, ferrocene as a metal catalyst precursor containing Fe atoms and thiophene as a promoter were introduced into a continuous flow of carrier gas in a once-through reactor whose temperature was controlled at 400°C to 700°C. A mixture of nitrogen and argon was used as the carrier gas. The flow rate of the carrier gas was 30,000sccm. By maintaining the temperature in the flow-through reactor within the above range, the metal catalyst precursor was produced as a particulate metal catalyst. The region in which the metal catalyst was produced is referred to as the first temperature zone.

[0127] The carbon source, methane, was then released into the carrier gas stream. The metal catalyst and carbon source were fed into a second temperature zone downstream of the first temperature zone, which was temperature-controlled at 1400° C. The second temperature zone was maintained at a temperature sufficient to produce carbon nanotube aggregates.

[0128] In the second temperature zone, an electric field was generated within the temperature-controlled flow reactor, which produced fibrous ULMWCNT aggregates. The aggregates were continuously discharged through the outlet of a flow-type reactor whose temperature was controlled at 100°C to 500°C, and the carbon nanotube aggregates were collected as fibrous ULMWCNT aggregates by continuous discharge. The obtained fibrous ULMWCNT aggregate contains ULMWCNT and MWCNT. The obtained fibrous ULMWCNT aggregate was washed with deionized water for 10 seconds in order to adjust the content ratio of Fe atoms, thereby obtaining a fibrous ULMWCNT aggregate 2.

[0129] 2. Preparation of Dispersion 2 Using the obtained fibrous ULMWCNT aggregate 2, a dispersion 2 was obtained in the same manner as in Example 1. However, the fibrous ULMWCNT aggregate 2 was cut with scissors to a length of about 1 cm before mixing so that the fibrous ULMWCNT aggregate 2 would not become entangled with the blades of the homogenizer.

[0130] 3. Evaluation In measuring the tensile strength, the fibrous ULMWCNT aggregate 2 of Example 2 was cut to a length of 100 mm, fixed to the gripping portion of a tensile testing device (manufactured by Shimadzu Corporation, Autograph AG-IS), and a tensile test was performed at a speed of 1 mm / min using a thin wire gripper (manufactured by Shimadzu Corporation). Except for this, evaluation was performed in the same manner as in Example 1 for the fibrous ULMWCNT aggregate 2 of Example 2 and the dispersion 2. The results are shown in Table 1.

[0131] Comparative Example 1 1. Production of sheet-like ULMWCNT aggregates 3 The sheet-like ULMWCNT aggregate collected in Example 1 was immersed in a polytetrafluoroethylene (PTFE) tray containing hydrochloric acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., special grade reagent) for 24 hours. Thereafter, the sheet-like ULMWCNT aggregate was removed from the tray and washed with deionized water until the pH of the washing water reached 7, thereby obtaining a sheet-like ULMWCNT aggregate 3.

[0132] 2. Preparation of Dispersion 3 Using the obtained sheet-shaped ULMWCNT aggregate 3 of Comparative Example 1, a dispersion liquid 3 was obtained in the same manner as in Example 1.

[0133] 3. Evaluation The sheet-shaped ULMWCNT aggregate 3 and dispersion liquid 3 of Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The results are shown in Table 1.

[0134] Comparative Example 2 1. Preparation of Powdered MWCNT Aggregates 1 As the powdered MWCNT aggregate 1, "multi-walled carbon nanotubes" (catalog number: FT7000, manufactured by C-nano Corporation) were prepared.

[0135] 2. Preparation of Dispersion 4 Dispersion liquid 4 was obtained in the same manner as in Example 1 using the powdered MWCNT1 of Comparative Example 2.

[0136] 3. Evaluation In measuring the tensile strength, the dispersion 4 was poured onto a slide glass type silicon plate (Dosaka EM Co., Ltd., #08-1044) of 22 mm × 75 mm × 3 mm, heated to 100 ° C and dried to prepare a measurement sample, which was fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. Except for this, the powdered MWCNT aggregate 1 of Comparative Example 2 and the dispersion 4 were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0137] Comparative Example 3 1. Preparation of Powdered MWCNT Aggregates 2 As the powdered MWCNT aggregate 2, "multi-walled carbon nanotubes" (catalog number: FT6120, manufactured by C-nano Corporation) were prepared.

[0138] 2. Preparation of Dispersion 5 Using the powdered MWCNT aggregate 2 of Comparative Example 3, a dispersion liquid 5 was obtained in the same manner as in Example 1.

[0139] 3. Evaluation In measuring the tensile strength, the dispersion 5 was poured onto a slide glass type silicon plate (Dosaka EM Co., Ltd., #08-1044) of 22 mm × 75 mm × 3 mm, heated to 100 ° C and dried to prepare a measurement sample, which was fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. Except for this, the powdered MWCNT aggregate 2 of Comparative Example 3 and the dispersion 5 were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0140] Comparative Example 4 1. Preparation of Powdered SWCNT Aggregates 1 As the powdered SWCNT aggregate 1, "single-walled carbon nanotubes" (catalog number: TUBALL, manufactured by OCSiAl Corporation) were prepared.

[0141] 2. Preparation of Dispersion 6 As the dispersion liquid of the powdered SWCNT aggregate 1 of Comparative Example 4, Dispersion Liquid 6 [product name: TUBALL TM BATT H2O, single-walled carbon nanotube aqueous solution, manufactured by OCSiAl Corporation] was used. The CNT concentration was adjusted to 0.2 mass%.

[0142] 3. Evaluation In measuring the tensile strength, the dispersion 6 was poured onto a slide glass type silicon plate (Dosaka EM Co., Ltd., #08-1044) of 22 mm × 75 mm × 3 mm, heated at 100°C and dried to prepare a measurement sample, which was fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. Except for this, the powdered SWCNT aggregate 1 of Comparative Example 4 and the dispersion 6 were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0143] [Table 1]

[0144] As shown in Table 1, the sheet-like ULMWCNT aggregate 1 (Example 1) and the fibrous ULMWCNT aggregate 2 (Example 2) of the examples are ULMWCNT aggregates that have a tendency to easily entangle with one another, and therefore have high electrical conductivity, and since the content ratio of Fe atoms is 0.5 mass% or more and less than 10 mass%, the Rsp value of the obtained dispersion is high, affinity with the dispersion medium is good, and the viscosity shows a value that is practically problem-free. From this, it can be seen that the aggregates of the examples have high electrical conductivity and good dispersibility in the dispersion medium.

[0145] On the other hand, the sheet-like ULMWCNT aggregate 3 (Comparative Example 1) of the comparative example, in which the content ratio of Fe atoms is less than 0.5 mass%, is a ULMWCNT aggregate that has a property of easily entangling with one another, and therefore has high electrical conductivity. However, since the contact between multiple ULMWCNTs is not adequately hindered by the Fe atoms and aggregation is not suppressed, the Rsp value of the obtained dispersion is low, there is a problem with affinity to the dispersion medium, and the viscosity, particularly at a shear rate of 100 s -1 It can be seen that the value of is high and at a level that is problematic for practical use. Therefore, it can be seen that the dispersibility in the dispersion medium is inferior to that of the aggregate of the Example. It is found that the comparative examples, powdered MWCNT aggregate 1 (Comparative Example 2) and powdered MWCNT aggregate 2 (Comparative Example 3), have low electrical conductivity due to their short maximum length and poor entanglement. In addition, because of the poor entanglement, the MWCNTs are less likely to aggregate, and regardless of the Fe atom content, the Rsp value of the obtained dispersion is low, there is a problem with the affinity with the dispersion medium, and the viscosity is low, which is at a level that is problematic for practical use. It can be seen that the powdered SWCNT aggregate 1 of the comparative example (Comparative Example 4) is SWCNT and therefore has higher electrical conductivity than MWCNT. However, SWCNTs tend to aggregate more than MWCNTs, and even if the content ratio of Fe atoms is increased to 10.0 mass% or more, SWCNT aggregation is not suppressed, so the Rsp value of the obtained dispersion is low, there is a problem with the affinity with the dispersion medium, and the viscosity value is high, which is at a level that is problematic for practical use.

Claims

1. A multi-walled carbon nanotube having a maximum length of 1000 μm to 30000 μm; Fe atoms, An aggregate of multi-walled carbon nanotubes, in which the content ratio of Fe atoms to the total mass of the aggregate is 0.5 mass % or more and less than 10 mass %.

2. The aggregate of multi-walled carbon nanotubes according to claim 1 , which is a conductive assistant.

3. A multi-walled carbon nanotube dispersion comprising the aggregate of multi-walled carbon nanotubes according to claim 1 or 2 and a dispersion medium.

4. A conductive material comprising the multi-walled carbon nanotube aggregate according to claim 1 or 2.

5. The multi-walled carbon nanotube dispersion according to claim 3, which is an ink composition for forming a negative electrode of a lithium battery.

6. An electrode comprising an electrode active material and the conductive material according to claim 4 .

7. A secondary battery comprising the electrode according to claim 6.

8. Multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa; Fe atoms, An aggregate of multi-walled carbon nanotubes, in which the content ratio of Fe atoms to the total mass of the aggregate is 0.5 mass % or more and less than 10 mass %.

9. A planar aggregate comprising the multi-walled carbon nanotube aggregate according to claim 1 , 2 or 8 .

10. A filter using the planar assembly according to claim 9.

11. 10. An electromagnetic wave shield using the planar assembly according to claim 9.

12. A pellicle for extreme ultraviolet rays using the planar assembly according to claim 9.

Citation Information

Patent Citations

  • Carbon nanotube assembly wire, carbon nanotube assembly wire bundle and carbon nanotube structure body

    WO2020138379A1

Cited By

  • Carbon nanotube aggregate, conductive material, electrode, secondary battery, planar aggregate, filter, electromagnetic wave shield and pellicle for extreme ultraviolet rays, and measurement method

    JP7792040B1

  • Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, and pellicles for extreme ultraviolet radiation.

    JP7868237B1

  • Carbon nanotube aggregate, conductive material, electrode, secondary battery, planar aggregate, filter, electromagnetic wave shield, pellicle for extreme ultraviolet rays, and measurement method

    WO2026203947A1